KONSTRUKSI KEPEMIMPINAN PERSPEKTIF MASLAHAH - St. Halimang (IAIN Kendari, 2018)
This study aims to determine the construction of leadership in the perspective of maslahah. This is the development of Islamic legal thought, the theory used in this study is theory of maslahat and Sadd azz>’ah. data collected by quoting, adapting and analyzing the literature that the relevance of the issues discussed, then all of them were reviewed and concluded. The results show that leadership must have the ability to direct the behavior of others, have certain skills that are not owned by everyone, so as to solve the problems that arise in the life of mankind. Between leaders and those who are led must establish synergic relations between the people and the government in carrying out their responsibilities. Between the two parties there was a synergy and mutual protection. Construction Leaders found several criteria, namely: (a) Principle of Deliberation (b) Justice, Preservation of absolute justice between fellow humans (c) Principle of Equality by treating something no more and no less. (d) The principle of humanity, namely everything worthy for humans to each other (e) Honesty, by proving between his words and deeds (f) Al-amanah, preserving the principle of being responsible both personally and institutionally (g) Al-tablig (openness), open openness to input from the people by absorbing all of his aspirations, (h) Al-fatha> nah (intelligence) intelligence, mastering conditions and insight, want to be under which the nation is. Privileges of a just leader because Fair is the noblest characteristic that determines the policies of a leader and even that raises the image and authority of a leader.